THE CAUSES OF PROS AND CONS IN DIVIDING INHERITANCE TWO TO ONE BY USING THE PERSPECTIVE OF JUSTICE PRINCIPLE TAFSEER - Anisa Nurfauziah; Eni Zulaiha; Nazar Fadli (Universitas Muhammadiyah Surakarta, 2023)
This study discussed the pros and cons of two-to-one inheritance using the principle of fair interpretation. The method used in this research was qualitative with library research, including finding sources from written materials with a historical approach. The discussion results included the sources of the argument for inheritance in the Qur'an, the distribution of inheritance one to two (1: 2) between men and women according to contemporary scholars and scholars, and the concept of justice put forward by the scholars. This study concluded that the reason for the pros and cons was the existence of different paradigms in interpreting the term justice. Classical scholars agree that inheritance verses are qath'i verses whose distribution cannot be contested so that the distribution of inheritance two to one is considered fair based on the responsibilities borne by a man. Meanwhile, feminist commentators consider the inheritance verse a sociological verse where the division of inheritance cannot ignore the current social context. The distribution of inheritance could change by the context of the circumstances and the benefits of the inheritance itself.